The Role of Self-Confidence and Self-Control in Fear of Missing Out (FoMO) Among High School Students - Heri Febri Yadi; Nurfarhanah Nurfarhanah (Journal of Educational, Health and Community Psychology, 2024)
Fear of missing out (FoMO) has become a significant issue experienced by internet users. However, research on FoMO has not been extensively explored. Therefore, the current study examines whether there is a relationship between self-confidence and self-control on Fear of missing out. This is a quantitative study with a descriptive correlational design, involving a sample of 164 students. The result show that self-confidence is significantly negatively correlated with fear of missing out. Addictionally, self control is also negatively correlated with Fear of missing out. Hence, in addressing FoMO, counselors need to enhance individuals’ self-confidence and self-control as protective strengths.